Vacuolar H+-ATPase is Down-regulated by the Angiogenesis-Inhibitory Pigment Epithelium-Derived Factor in Metastatic Prostate Cancer Cells - Sennoune, S. R.; Bermudez, L. E.; Lees, J. C.; Hirsch, J.; Filleur, S.; Martínez-zaguilán, R. (Cellular and Molecular Biology, 2014)
The Vacuolar H+-ATPases (V-ATPases), a multi-subunits nanomotor present in all eukaryotic cells resides in the endomembranes of exocytotic and endocytotic pathways. Plasmalemmal V-ATPases have been shown to be involved in tumor cell metastasis. Pigment epithelium-derived factor (PEDF), a potent endogenous inhibitor of angiogenesis, is down-regulated in prostate cancer cells. We hypothesized that the transduction of PEDF in prostate cancer cells will down-regulate V-ATPase function; that in turn will decrease the expression of the V-ATPase accessory protein ATP6ap2 and a-subunit isoforms that target V-ATPase to the cell surface. To test these hypotheses, we used the human androgen-sensitive prostate cancer cells LNCaP, and its castration-refractory-derivative CL1 that were engineered to stably co-express the DsRed Express Fluorescent Protein with or without PEDF. To determine if PEDF down-regulates the function of V-ATPase, we measured the rate of proton fluxes (JH+) of the cytosolic and endosome/lysosome compartments. The mRNA levels for subunit-a isoforms and the ATP6ap2 were measured using quantitative reverse transcription-PCR. The results showed that PEDF expression decreased the rate of JH+ in metastatic CL1 cells without affecting JH+ in non-metastatic LNCaP cells, when studying pHcyt. Interestingly, PEDF did not affect JH+ in endosomes/lysosomes either in metastatic cells or in non-metastatic cells. We also showed that PEDF significantly decreases the levels of a4 isoform and ATP6ap2 in metastatic CL1 cells, without affecting the levels of a4 isoform in the non-metastatic LNCaP cells. These data identify PEDF as a novel regulator of V-ATPase suggesting a new way by which PEDF may inhibit prostate tumor growth.